Deep Learning with PyTorch 1.x : Implement deep learning techniques and neural network architecture variants using Python, 2nd Edition /: Implement deep learning techniques and neural network architecture variants using Python, 2nd Edition. (2019) - Mitchell, Laura; K., Sri. Yogesh; Subramanian, Vishnu
No abstract available